Utilization and costs of postoperative physical therapy after multiligament knee surgery: a retrospective cross-sectional study. Issue 2 (13th March 2021) - Qin, Charles; Baker, Hayden; Qin, Mia M.; Athiviraham, Aravind
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: The aim of this study was to analyze the use of and charges related to physical therapy (PT) after multiligament knee surgery across different postoperative time points and to identify factors related to increased utilization. Methods: The Humana Claims Database was queried for all patients who underwent a multiligament knee reconstruction procedure. We identified patients with a PT-related Current Procedural Terminology (CPT) code at 14 days, 30 days, 90 days, and 6 mo postoperatively. The mean charge per patient and mean number of billed encounters were analyzed. Chi-square and linear regression analysis were used to identify factors related to increased PT utilization. Results: Data for 497 patients undergoing multiligament knee reconstruction surgery was available. The number of patients utilizing PT at 14 days, 30 days, 90 days, and 6 mo after surgery was 315, 423, 484, and 497, respectively. The mean cost of PT in these groups were $315.65, $580.05, $1490.55, and $1796.52, respectively. The mean number of visits were 6, 12, 32, and 38, respectively. Patients with subsequent surgery for arthrofibrosis had significantly higher mean cost ($3528.40 vs. $1546.43; P <0.001) and higher mean number of visits (73 vs. 35; P <0.001) than those without. When compared with patients without a diagnosis of knee dislocation, patients with a knee-disclocation diagnosis had significantly higher mean cost ($2204.85 vs. 1627.45; P <0.001) and higher mean number of visits (43 vs. 31; P <0.001). Finally, privately insured patients had higher mean cost ($1933.07 vs. $1051.70) and mean number of visits (40 vs. 25) than publicly insured patients. Regression coefficients were $-390.86 for obesity, $409.50 for knee dislocation, $807.53 for private insurance, and $1845.00 for surgery for arthrofibrosis. Conclusions: There was increased utilization of PT among patients who had a diagnosis of knee dislocation, those who required surgery for arthrofibrosis, and those who had private insurance after multiligament knee reconstruction surgery. Level of Evidence: Level III.